2013
DOI: 10.5216/cab.v14i2.17926
|View full text |Cite
|
Sign up to set email alerts
|

Características Do Parto E Involução Uterina Em Ovelhas Nativas Do Pantanal Brasileiro

Abstract: The aim of this study was to describe aspects of the parturition and uterine involution in native sheep from Brazilian Pantanal. Fifty-seven pluriparous ewes were used in this study. At parturition, the placenta expulsion (h), weight (g), total diameter of cotyledons, sex and weight of newborn, and single or twin parturition were evaluated. The uterine involution was evaluated by leucocytes profile, desquamation cells (cervix-uterine smears) and transrectal ultrasonography at 1, 7, 14, 21 and 28 days post-part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Mc Entee [25] reported that it takes a long period of time, even up to 49 days in ewes according to his histological findings. On the contrary, involution process was reported to be ended between 14-21 days in native Pantanal sheep [13]. Many variables like breed, lambing season, parity and suckling may affect the duration of postpartum period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mc Entee [25] reported that it takes a long period of time, even up to 49 days in ewes according to his histological findings. On the contrary, involution process was reported to be ended between 14-21 days in native Pantanal sheep [13]. Many variables like breed, lambing season, parity and suckling may affect the duration of postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…Ovine uterine involution has been investigated intensely by B-mode ultrasonography [13,17,19,20,26,40]. Finally, researches performed on Doppler ultrasonography in ewes have gained momentum in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…In small ruminants, accurate evaluation of the internal organs of the reproductive tract by rectal palpation is not possible (Feliciano et al, 2013) and authors reported different intervals to complete uterine involution. Studies were conducted assessing hormonal levels (Ishwar, 1995), radiography (Tian and Noakes, 1991), ultrasonography (Fernandes et al, 2013), laparotomy (Rubianes et al, 1996) or evaluation after slaughtering (Rubianes and Ungerfeld, 1993).…”
Section: Postpartum Assessment Of the Genital Tract By Ultrasonographymentioning
confidence: 99%
“…The uterine lumen and its content in a normal uterus can be easily visualized during the early stage of the puerperium, appearing enlarged and with heterogeneous echotexture due to the observation of the layers (Hauser and Bostedt, 2002), presenting up to 10 cm of diameter (Fernandes et al, 2013). As its size decreases progressively, it may be more difficult to image it after the 13 th day post-partum by transabdominal scanning, as reported by Ababneh and Degefa (2005).…”
Section: Postpartum Assessment Of the Genital Tract By Ultrasonographymentioning
confidence: 99%
“…The reproductive potential of ewes (Ovis aries L.) is closely related to the early resumption of cyclic ovarian activity after lambing (Fernandes et al, 2013). For this reason, it is necessary to manage the most important factors that inhibit post-partum ovarian activity, namely breastfeeding and nutrition (Orihuela et al, 2016).…”
Section: Introductionmentioning
confidence: 99%